2002
DOI: 10.1152/japplphysiol.00612.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of respiratory muscle unloading on exercise-induced diaphragm fatigue

Abstract: We previously compared the effects of increased respiratory muscle work during whole body exercise and at rest on diaphragmatic fatigue and showed that the amount of diaphragmatic force output required to cause fatigue was reduced significantly during exercise (Babcock et al., J Appl Physiol 78: 1710, 1995). In this study, we use positive-pressure proportional assist ventilation (PAV) to unload the respiratory muscles during exercise to determine the effects of respiratory muscle work, per se, on exercise-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 20 publications
2
111
0
Order By: Relevance
“…Previous investigations demonstrated that respiratory muscle unloading during high-intensity exercise can prevent respiratory muscle fatigue and the reflex vasoconstriction within active locomotor muscles, and can ultimately lead to increased limb blood flow (Babcock et al 2002;Chiappa et al 2009;Harms et al 1997;Romer et al 2006). Although in normal subjects, this phenomenon may not happen during submaximal exercise (Wetter et al 1999), it could occur in obese patient population characterized by a substantially higher work of breathing and increased metabolic demands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations demonstrated that respiratory muscle unloading during high-intensity exercise can prevent respiratory muscle fatigue and the reflex vasoconstriction within active locomotor muscles, and can ultimately lead to increased limb blood flow (Babcock et al 2002;Chiappa et al 2009;Harms et al 1997;Romer et al 2006). Although in normal subjects, this phenomenon may not happen during submaximal exercise (Wetter et al 1999), it could occur in obese patient population characterized by a substantially higher work of breathing and increased metabolic demands.…”
Section: Discussionmentioning
confidence: 99%
“…Expiration becomes active which requires larger muscle recruitment, and a larger amount of oxygen demanding an increase in blood flow (Babcock et al, 2002;Johnson et al, 1993;Witt et al, 2007). Evidence suggests that the demand for an increase in blood flow to the respiratory muscles during maximal or heavy exercise "steals" blood flow from the other exercising muscles through sympathetically mediated vasoconstriction (Harms et al, 1998;St.…”
Section: Discussionmentioning
confidence: 99%
“…Thus future studies are needed to determine the role these factors may play in the loss of function associated with fatigue. a mechanical ventilator (11). However, other factors besides respiratory muscle work must also be responsible for exerciseinduced respiratory muscle fatigue, because fatigue did not occur when the resting subject mimicked the magnitude and duration of diaphragmatic work incurred during exercise (13).…”
Section: Exercise-induced Respiratory Muscle Fatiguementioning
confidence: 99%